Perioperative cefuroxime pharmacokinetics in cardiac surgery (Clinics, 2007)
OBJECTIVE: The objective was to investigate the plasma levels and to compare the pharmacokinetics of cefuroxime during and after surgery in adult patients with elective indication for coronary artery bypass grafting. METHODS: Seventeen patients received three 1.5-g bolus IV doses of cefuroxime, one every 12 hrs. Serial blood samples (3 mL) were collected 1, 3, 6, 9, and 12 hrs after the first dose (given during the intervention) and after the second and third doses (postsurgery). Blood samples were centrifuged and stored frozen until being assayed. For assessment of the cefuroxime plasma levels by liquid chromatography, only 200 µL of plasma were required. Determination of cefuroxime plasma levels was followed by a pharmacokinetic (PK)-modeling using PK Solutions 2.0 software. RESULTS: The kinetic parameters obtained remained unchanged after the first, second, and the third dose as follows: elimination half-life: 1.8 h, 1.9 h, and 1.8 h; clearance: 1.4, 1.5, and 1.5 mL/min/kg, respectively. Additionally, the apparent volume of distribution did not change during and after the intervention: 0.19, 0.25, and 0.22 L/kg, after the first, second, and the third dose, respectively. Since the drug has a low volume of distribution, plasma levels obtained after a 1.5-g IV bolus injection of cefuroxime decreased rapidly due to the high plasma clearance, with a consequent short half-life. CONCLUSIONS: The kinetic disposition of cefuroxime remains unaltered in patients undergoing coronary artery bypass grafting; to reduce the fluctuation in plasma concentrations so that the antibiotic prophylaxis in the peri-operative period is guaranteed, the dose regimen should be reviewed.